PERILAKU WISATAWAN KULINER GENERASI Z DI YOGYAKARTA - Septi Sedyaning Hanurani (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
Generation Z is the target market for future tourism because they constitute the largest share of the world's population. For Generation Z travelers, culinary experiences are an important aspect of tourism. This research aims to explain the culinary tourism behavior of Generation Z in Yogyakarta, including their goals, visit frequency, culinary preferences, social media use, and desire to revisit culinary tourism destinations. This study was conducted through a survey of 394 members of Generation Z who have engaged in culinary tourism in Yogyakarta. The research results show that one of the main tourist attractions for the respondents is culinary experiences, and they have engaged in culinary tourism more than three times. According to the survey, 72.2% of respondents chose Yogyakarta as their favorite culinary destination. The social media platforms most used to search for culinary information are Instagram and TikTok. The local restaurants in Yogyakarta favored by Generation Z are Gudeg Yu Djum and Kopi Klotok. The motivation of Generation Z culinary tourists when deciding to revisit a culinary destination is to obtain sensory experiences such as taste, aroma, texture, and appearance of the food. The research results show that food quality, real experiences, and the use of social media as a source of travel information influence the culinary tourism behavior of Generation Z.